A Control Algorithm for Electric Vehicle Fast Charging Stations Equipped With Flywheel Energy Storage Systems - Bo Sun; Dragicevic, Tomislav; Freijedo, Francisco D.; Vasquez, Juan C.; Guerrero, Josep M. (IEEE transactions on power electronics, 2016)
This paper proposes a control strategy for plug-in electric vehicle (PEV) fast charging station (FCS) equipped with a flywheel energy storage system (FESS). The main role of the FESS is not to compromise the predefined charging profile of the PEV battery during the provision of a hysteresis-type active power ancillary service to the overhead power system. In that sense, when the active power is not being extracted from the grid, an FESS provides the power required to sustain the continuous charging process of the PEV battery. A key characteristic of the whole control system is that it is able to work without any digital communication between the grid-tied and FESS converters. Detailed system modeling and dynamics analysis of the controller are carried out for the different operating modes of the FCS system. A lab-scale prototype was built to validate the proposal. The presented experimental results proved the high accuracy of the theoretical analysis.